Bright ferritin for long-term MR imaging of human embryonic stem cells - Keyu Zhuang; Rocco Romagnuolo; Tamilla Sadikov Valdman; Kyle D. W. Vollett; Daniel A. Szulc; Hai-Ying Mary Cheng; Michael A. Laflamme; Hai-Ling Margaret Cheng (Stem Cell Research & Therapy, 2023)
Abstract Background A non-invasive imaging technology that can monitor cell viability, retention, distribution, and interaction with host tissue after transplantation is needed for optimizing and translating stem cell-based therapies. Current cell imaging approaches are limited in sensitivity or specificity, or both, for in vivo cell tracking. The objective of this study was to apply a novel ferritin-based magnetic resonance imaging (MRI) platform to longitudinal tracking of human embryonic stem cells (hESCs) in vivo. Methods Human embryonic stem cells (hESCs) were genetically modified to stably overexpress ferritin using the CRISPR-Cas9 system. Cellular toxicity associated with ferritin overexpression and manganese (Mn) supplementation were assessed based on cell viability, proliferation, and metabolic activity. Ferritin-overexpressing hESCs were characterized based on stem cell pluripotency and cardiac-lineage differentiation capability. Cells were supplemented with Mn and imaged in vitro as cell pellets on a preclinical 3 T MR scanner. T1-weighted images and T1 relaxation times were analyzed to assess contrast. For in vivo study, three million cells were injected into the leg muscle of non-obese diabetic severe combined immunodeficiency (NOD SCID) mice. Mn was administrated subcutaneously. T1-weighted sequences and T1 mapping were used to image the animals for longitudinal in vivo cell tracking. Cell survival, proliferation, and teratoma formation were non-invasively monitored by MRI. Histological analysis was used to validate MRI results. Results Ferritin-overexpressing hESCs labeled with 0.1 mM MnCl2 provided significant T1-induced bright contrast on in vitro MRI, with no adverse effect on cell viability, proliferation, pluripotency, and differentiation into cardiomyocytes. Transplanted hESCs displayed significant bright contrast on MRI 24 h after Mn administration, with contrast persisting for 5 days. Bright contrast was recalled at 4–6 weeks with early teratoma outgrowth. Conclusions The bright-ferritin platform provides the first demonstration of longitudinal cell tracking with signal recall, opening a window on the massive cell death that hESCs undergo in the weeks following transplantation before the surviving cell fraction proliferates to form teratomas.